Welding Training for Assisted Communities at Tanjungpati Children's Special Correctional Institution - Allen, Rio Valery; Ernita, Yuni; Novita, Sri Aulia; Djinis, Musdar Effy; Herdian, Fithra; Zulnadi, Zulnadi; Batubara, Fanny Yuliana (Institut Teknologi Nasional, Bandung, 2026)
The juvenile correctional system (LPKA) in Indonesia carries out a fundamental mandate to rehabilitate correctional students (Andikpas) and prevent the recurrence of criminal acts (recidivism). A crucial instrument in correctional rehabilitation is competency-based vocational training. This study aims to analyze the theoretical relevance of the Shielded Metal Arc Welding (SMAW) welding training program based on the Indonesian National Work Competency Standard (SKKNI) at LPKA, identify existing structural implementation challenges, and formulate optimization strategies through a collaborative model. The results of the analysis show that welding training is a very effective strategic program. The industrial sector in Indonesia needs at least 45,000 welding experts, proving the high demand for the job market. These skills serve as a powerful catalyst to achieve desistance by providing the human capital needed to get a stable job, thus overcoming the job instability associated with the risk of repeat crime. Despite having great potential, the implementation of coaching programs at LPKA is hampered by limited funds, inadequate facilities, and a lack of expert instructor Human Resources (HR). To overcome this obstacle, it is recommended to adopt a Mutualistic Partnership model with external parties, which aims to ensure the standardization of the 320 Hours of Training (JP) curriculum in accordance with SKKNI, competency certification, and integration of vocational work readiness measurements. This partnership creates mutual benefits and strengthens LPKA's capacity on an ongoing basis.